Increased Added Sugar Consumption Is Common in Parkinson's Disease - Palavra, Natalie C.; Lubomski, Michal; Flood, Victoria M.; Davis, Ryan L.; Sue, Carolyn M. (Frontiers in Nutrition, 2021)
Objectives: There is limited information about the dietary habits of patients with Parkinson’s Disease (PD), or associations of diet with clinical PD features. We report on patterns of nutritional intake in an Australian PD cohort. Methods: 103 PD patients and 81 healthy controls (HCs) completed a validated semi-quantitative food frequency questionnaire. Food and nutrient intake was quantified, with consideration of micronutrients and macronutrients (energy, protein, carbohydrate, fat, fibre and added sugar). Participants also completed PD-validated non-motor symptom questionnaires to determine any relationships between dietary intake and clinical disease features. Results: Mean daily energy intake did not differ considerably between PD patients and HCs (11131 kJ/day versus 10188 kJ/day, p=0.241). However, PD patients reported greater total carbohydrate intake (279 g/day versus 232 g/day, p=0.034). This was largely attributable to increased daily sugar intake (153 g/day versus 119 g/day, p=0.003) and in particular free sugars (61 g/day versus 41 g/day, p=0.001). PD patients who 1) experienced chronic pain, 2) were depressed, or 3) reported an impulse control disorder, consumed more total sugars than HCs (all p<0.05). Increased sugar consumption was associated with an increase in non-motor symptoms, including poorer quality of life, increased constipation severity and greater daily levodopa dose requirement. Conclusions: We provide clinically important insights into the dietary habits of PD patients that may inform simple dietary modifications that could alleviate disease symptoms and severity. The results of this study support clinician led promotion of healthy eating and careful management of patient nutrition as part of routine care.